Relics @ the lab : an analytical approach to the study of relics (Interdisciplinary studies in ancient culture and religion, 2018)
Back cover: The book Relics @ the Lab, an Analytical Approach to the Study of Relics includes a series of studies presented at the first international workshop Relics @ the Lab organized by the Royal Institute of Cultural Heritage (KIK-IRPA) in Brussels, Belgium (27-28 October 2016). The papers cover a large variety of themes as well as analytical methods. Some papers focus on the primary relics while others deal with the nature and origin of secondary as well as tertiary relics. The first group of papers emphases on the archaeological authenticity of the relics, the second group elucidate the use, additions and manipulations of the relics through the ages. The applied analytical techniques are very divers. Radiocarbon and physical anthropology are the main tools to study the primary relics, while dye analysis, imaging techniques, textile analysis and dendrochronology are used to study the secondary and tertiary relics. Sometimes unexpected techniques, like the analysis of writing ink or the determination of plants and excrements, complete the wide range of analytical methods used to understand the origin, nature and context of the relics. Academics as well as professionals working in archaeology, art history, museum labs and conservation sciences will find this an invaluable reference source.